2011
DOI: 10.1111/j.1574-6968.2011.02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Cra negatively regulates acid survival in Yersinia pseudotuberculosis

Abstract: Survival in acidic environments is important for successful infection of gastrointestinal pathogens. Many bacteria have evolved elaborate mechanisms by inducing or repressing gene expression, which subsequently provide pH homeostasis and enable acid survival. In this study, we employed comparative proteomic analysis to identify the acid-responsive proteins of a food-borne enteric bacterium, Yersinia pseudotuberculosis. The expression level of eight proteins involved in carbohydrate metabolism was up- or downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…While the cra gene (originally designated fruR) is adjacent to the fructose operon fruBKA in Pseudomonas putida (43), this gene (B1H58_03575) lies far away from fruBKA (B1H58_14040 to B1H58_14050) in P. alhagi LTYR-11Z, in line with members of enteric bacteria, such as E. coli and Yersinia pseudotuberculosis (43,44,59). It has been reported that carbon nutrition influences colonization and maintenance of pathogenic and commensal E. coli strains in the mouse intestine (60)(61)(62), while the pathogenic EHEC O157:H7 strain required gluconeogenic nutrients to successfully colonize the intestines precolonized with the commensal E. coli Nissle 1917 (63).…”
Section: Discussionmentioning
confidence: 99%
“…While the cra gene (originally designated fruR) is adjacent to the fructose operon fruBKA in Pseudomonas putida (43), this gene (B1H58_03575) lies far away from fruBKA (B1H58_14040 to B1H58_14050) in P. alhagi LTYR-11Z, in line with members of enteric bacteria, such as E. coli and Yersinia pseudotuberculosis (43,44,59). It has been reported that carbon nutrition influences colonization and maintenance of pathogenic and commensal E. coli strains in the mouse intestine (60)(61)(62), while the pathogenic EHEC O157:H7 strain required gluconeogenic nutrients to successfully colonize the intestines precolonized with the commensal E. coli Nissle 1917 (63).…”
Section: Discussionmentioning
confidence: 99%
“…Stingl and De Reuse (2005) have reported that Y. pseudotuberculosis uses urease (UreABC) to convert urea to ammonia that neutralizes H + for acid tolerance. Recently, Hu et al have shown that the regulator Cra negatively regulates acid tolerance in Y. pseudotuberculosis (Hu et al, 2011). Recently, Hu et al have shown that the regulator Cra negatively regulates acid tolerance in Y. pseudotuberculosis (Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A Y. pseudotuberculosis enzyme involved in aspartate metabolism (AspA) also plays a role in acid survival (Hu et al, 2010). Recently, Hu et al have shown that the regulator Cra negatively regulates acid tolerance in Y. pseudotuberculosis (Hu et al, 2011). In addition, two-component regulon assays have revealed that several regulators, including PhoP, OmpR and PmrA, control acid survival in Y. pseudotuberculosis (Flamez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other bacterial factors that promote survival under acidic conditions include urease [126], TatC [127], PhoP, OmpR, and PmrA [128, 129]. Acidic pH also induces a downregulation of the transcriptional regulator, Cra (for catabolite repressor/activator), which increases bacterial acid survival [130]. Presumably Cra mediates this action via transcriptional regulation, but its mechanism of action remains unknown.…”
Section: Introductionmentioning
confidence: 99%